2020
DOI: 10.1186/s12912-020-00489-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of empowered work environments on the psychological experiences of nursing assistants during COVID-19: a qualitative study

Abstract: Background Nursing Assistants (NA) who feel empowered tend to perform their duties better, have higher morale and job satisfaction, and are less likely to leave their jobs. Organizational empowerment practices in hospitals likely shape the psychological experiences of empowerment among these personnel; however, little is known about this relationship. Objective We used qualitative inquiry to explore the relationship between organizational empowerment structural components and feelings of psychological empowe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 22 publications
1
38
0
2
Order By: Relevance
“…Improving the employment outlook of CNA and EVS nursing home staff members may help ensure nursing home capacity and employee retention, as participants reported quickly burning out under the added pressure of an ongoing pandemic. Empowering CNAs has previously been associated with increased staff retention in US nursing homes [ 12 ] and a qualitative study with CNAs found the availability of resources, such as equipment and staffing, may help to enable coping with the increased emotional burden of the COVID-19 pandemic [ 13 ]. One observation of note from our findings was that when a participant stated they had received hazard pay, or other financial incentive for working during the pandemic, they tended to make more positive statements about their facility and its overall handling of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Improving the employment outlook of CNA and EVS nursing home staff members may help ensure nursing home capacity and employee retention, as participants reported quickly burning out under the added pressure of an ongoing pandemic. Empowering CNAs has previously been associated with increased staff retention in US nursing homes [ 12 ] and a qualitative study with CNAs found the availability of resources, such as equipment and staffing, may help to enable coping with the increased emotional burden of the COVID-19 pandemic [ 13 ]. One observation of note from our findings was that when a participant stated they had received hazard pay, or other financial incentive for working during the pandemic, they tended to make more positive statements about their facility and its overall handling of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an early study of remote work found that "it may be possible to enhance employees' work performance through management efforts to improve employees' remote work self-efficacy" (Staples et al, 1998). Elaborating further, a study during Covid-19 recommended creating "empowered environments ... by ensuring that employees have access to important information, resources, and support … and provid[ing] opportunities for growth and development" (Travers et al, 2020). Other researchers have focused on the virtues of "transformational leadership," with one study Considerations in the use of work-from-home (wfh) for post-pandemic planning and management describing transformational leaders as those who are able to "act as inspirational role models, consider their employees individually … [and who also] motivate their employees through an effective communication of a positive vision for the future" (Bark et al, 2016).…”
Section: Findings On Effective Management Of Work-from-homementioning
confidence: 99%
“…Begreppet egenmakt används även i sammanhang där avsikten är att stärka vårdares moraliska och etiska förhållningssätt (Khoshmehr, Barkhordari-Sharifabad, Nasiriani & Fallahzadeh 2020;Travers, Schroder, Norful & Aliyu 2020). Ny forskning visar att begreppet egenmakt kan användas för att beskriva utvecklingen av strukturella system som möjliggör en vårdares välbefinnande (Roji & Jooste 2018).…”
Section: Egenmaktunclassified